Towards Ecological Justice: Perspectives on Islamic Law and Deep Ecology Environmental Ethics in Overcoming The Environmental Crisis: , - Rizaldy, Wahyu Fahmi; Sopalo, Justino Ximenes Sopalo (Institut Agama Islam Negeri Kendari, 2026)
The increasingly urgent global environmental crisis demands effective, fair, and equitable solutions. The concept of ecological justice offers a crucial framework to achieve this goal. This framework fundamentally emphasizes the fair distribution of environmental benefits and burdens, secures the recognition of the rights of indigenous and local communities, and mandates inclusive participation in environmental decision-making. In this context, Islamic law presents a robust foundation for achieving this justice. Its principles are rooted in the human responsibility as 'caliphs' (stewards) of the Earth. This perspective is highly compatible with deep ecology's environmental ethics, which radically views nature as possessing intrinsic value, independent of human utility. This paper aims to develop a theoretical framework that integrates these two potent systems—Islamic law and deep ecology ethics—and subsequently applies this synthesized framework to real-world case studies. A normative legal method is employed to systematically analyze Islamic legal principles and doctrines relevant to ecological justice. The research results indicate that this integration provides comprehensive, ethically-grounded guidance for addressing the complex environmental crisis. This approach moves beyond mere conservation to champion true ecological justice. Principles within Islamic jurisprudence, such as the prohibition against destroying nature (fasad), the obligation to maintain ecosystem balance (mizan), and the concept of the rights of all living creatures, align closely with the core values of deep ecology, particularly the emphasis on interconnection and nature's intrinsic worth. Ultimately, the application of this theoretical framework in real case studies demonstrates its significant potential to create tangible, sustainable, and genuinely just environmental solutions that respect both human dignity and ecological integrity.